Landasan Filosofis-Teologis Kurikulum Pendidikan Agama Islam - Syahida Ajrina; Salamah Salamah (Lembaga Yasin AlSys, 2026)
The philosophical-theological foundation is the primary basis for designing and developing the Islamic Religious Education (PAI) curriculum because it determines the direction, values, and objectives of Islamic education. This study aims to examine the philosophical-theological foundation of the PAI curriculum by analyzing the relationship among the ontological, epistemological, and axiological aspects of Islamic education; the integration of revelation and reason; the Islamization of knowledge; scientific integration; and its implementation in contemporary Islamic education. This study used a qualitative approach with a library research design through the review and analysis of various literature sources, such as books, journals, and relevant scientific articles. The results show that the philosophical-theological foundation serves as an important foundation in developing a PAI curriculum oriented toward the balanced formation of students in intellectual, spiritual, moral, and social aspects. The integration of ontological, epistemological, and axiological aspects in the PAI curriculum affirms that Islamic education focuses not only on the transfer of religious knowledge but also on the formation of ways of thinking, attitudes, values, and actions aligned with Islamic principles. In addition, the concepts of integrating revelation and reason, the Islamization of knowledge, and scientific integration play a role in overcoming the dichotomy between religious sciences and general sciences, making the PAI curriculum more relevant to the needs of contemporary Islamic education. The conclusion of this study affirms that the philosophical-theological foundation has a strategic role in developing a PAI curriculum that is integrative, transformative, and responsive to the challenges of the times. The contribution of this study lies in strengthening the conceptual framework for developing a PAI curriculum based on philosophical-theological values in the context of contemporary Islamic education.